Região e regionalização: estudo da região metropolitana do Vale do Paraíba e litoral norte - Maria, Jéssica Marson [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
From the 1988 Federal Constitution, the creation and organization of metropolitan regions became the responsibility of the state governments, and each of these federal entities performs the regionalization process according to their own criteria and methods, which have not due clarity. In São Paulo, there are currently five metropolitan areas: metropolitan regions of RM de São Paulo, Santos, Campinas, Sorocaba, and the Vale of Paraíba and Litoral Norte (RMVale-LN), the latter being, the study area of this work. Strategically located between the two major Brazilian cities, São Paulo and Rio de Janeiro, the RMVale-LN has extensive road infrastructure, manufacturing and services, created in 2012 encompasses 39 municipalities that previously belonged to the administrative region of São José dos Campos. These municipalities have different realities, there intraregional inequalities that show that the process of becoming cities consider interests of external actors and not in fact the municipal realities, if the location is actually underground. This process metropolization the region alters the place administrative dynamic, because place governments must adapt bureaucratically and in everyday practice to this new instrument, endowed Agency, advice and unique Fund, which constitutes the metropolitan regions. Trying to understand these place changes as well as the actors and interests involved in this growing regionalization process in the state of São Paulo, this study was conducted

A partir da Constituição Federal de 1988, a criação e organização de regiões metropolitanas (RMs) tornou-se responsabilidade dos governos estaduais, e cada um destes entes federativos realiza o processo de regionalização de acordo com seus próprios critérios e métodos, os quais não possuem a devida clareza. No estado de São Paulo, há atualmente, 5 RMs: RM de São Paulo, Baixada Santista, Campinas, Sorocaba, e a do Vale do Paraíba e Litoral Norte (RMVale-LN), sendo esta última, a área de estudo deste trabalho. Localizada estrategicamente entre as duas maiores metrópoles brasileiras, São Paulo e Rio de Janeiro, a RMVale-LN conta com ampla estrutura viária, industrial e de serviços, criada em 2012 engloba os 39 municípios que pertenciam anteriormente a região administrativa de São José dos Campos. Estes municípios apresentam realidades locais diversas, há desigualdades intraregionais que evidenciam que o processo de metropolização considera interesses de agentes externos e não de fato as realidades municipais, se o local é de fato metropolitano. Este processo de metropolização da região altera as dinâmicas administrativas municipais, pois as prefeituras precisam se adaptar burocraticamente e na prática cotidiana a este novo instrumento, dotado de Agência, Conselhos e Fundo exclusivo, que se constitui a RM. Buscando compreender estas mudanças locais, bem como os agentes e interesses envolvidos neste processo de regionalização crescente no estado de São Paulo, este trabalho foi desenvolvido
Keywords: Geografia regional; Regiões metropolitanas; Planejamento urbano; Vale do Paraíba (SP e RJ)